The Impact of Mother Tongue-Based Education on School Readiness and Retention among Indigenous Children in Nepal - Chouhan, Tara (Kutumbha vani, 2025)
A lot of indigenous kids in Nepal still don’t get a real shot at early education. Sure, the country talks a big game there are strong policies like the School Sector Development Plan, and Nepal has signed big agreements, including the UN Declaration on the Rights of Indigenous Peoples. But what’s on paper and what actually happens in classrooms? That’s a whole different story. The real snag is language. Schools almost always teach in Nepali. So, kids who grow up speaking something else walk in already behind. They struggle, their confidence takes a hit, and way too many end up dropping out early.This paper takes a hard look at how language, culture, and real educational fairness get all tangled together. It focuses on mother tongue-based multilingual education (MTB-MLE), pulling from research, policy, and some pilot projects. The evidence is pretty clear: kids do better, remember more, and feel proud of who they are when they learn in their own language. If Nepal actually wants to see change, it needs to expand MTB-MLE programs, make more local learning materials, hire and support indigenous teachers, and give more control to local governments—especially now that the federal systems in place.But just having good policies isn’t going to cut it. Nepal has to invest in real teacher training, build a curriculum that includes everyone, and bring communities into the process. When indigenous voices and languages finally have a genuine place in early childhood education, then Nepal can start offering an education that’s fair—and that really fits its rich, diverse culture.